Diagnosis of chronic calculus cholecystitis using ultrasonography and co-related with per operative findings and histopathological findings in adult - Naser, Jamal Abdul; Hosssain, Md Afzal; Jahan, Shamima; Md Aminullah; Annee, Farjana Basher (Journal of Dhaka National Medical College & Hospital, 2025)
Background: Gall bladder diseases are most commonly secondary to cholelithiasis. While most cases of gall stones are asymptomatic, some cases may progress to severe symptomatic disease occasionally into malignancy. Early and accurate diagnosis allows prompt treatment and reduces both morbidity and other complications. Objectives: To access the clinical diagnosis of chronic cholecystitis using ultrasonography and corelation with per operative findings and histopathological examination findings. Methods: This is a descriptive type of observational study which was conducted at department of Surgery, Dhaka National Medical College Hospital, over a period of 12 months from 6th December 2017to 5th December 2018. Total 150 patients clinically diagnosed of chronic cholecystitis with laboratory profile, imaging proven in surgery department of Dhaka National Medical College Hospital were included. All patient underwent laparoscopic cholecystectomy but few patients needed conversion into open cholecystectomy due to severe adhesion with surrounding structures. Resected gall bladder was sent for histopathological examination. Comparison was done by tabulation and graphical presentation in the form of tables, pie chart, bar diagrams etc. Results: In this study, Ultrasonography findings revealed that, gallbladder size was normal in 97(64.66%), contracted in 47(31.33%), distended in 6(4%) patients. Most of the patients gall bladder wall thicknes was within normal limit (1-3 mm)found in 137(91.33%) who is diagnosed clinically as a case of chronical culus cholecystitis. Thick wall gall bladder found in 13(8.66%) patients.Gallbladder contains multiple stone in 99(66%), single stone in 32(21.33%), biliary sludge in 19 (12.66%) patients. Both Wall-Echo-Shadow and Peri-cholecystitic fluid was present in 4(2.6%) patients separately. Per operatively, Gall bladder found distended in 9(6%) patients among them 7(4.66%) were mucocele and 2(1.33%) were empyema. Normal sized gall bladder found in 92 (61.33%) and contracted in 49(32.66%) patients. Normal wall thickness found 126(84%) patients and rest 24(16%) had thick gall bladder wall. Gallbladder contains multiple stone in 102(68%) patients. Single stone and biliary sludge found in 29(19.33%) and 19(12.66%) respectively. No adhesion presents in 39(26%) cases and adhesions in Callot's triangle found in 47.33%. Adhesions with inferior surface of liver, non visualisation of Callot's triangle anatomy and partially intrahepatic gall bladder found in 14.66%, 09.33% and 02.66% patients respectively. Due to difficulty, 7(4.66%) cases need to convert into open cholecystectomy. Histopathological findings revealed that, 135 (90%) specimens showed evidence chronic cholecystitis, 9.33% acute cholecystitis. Only 1 (0.66%) gallbladder showed evidence of adenocarcinoma of papillary variety along with cholelithiasis. Conclusions: Ultrasonography is a good diagnostic tool in the diagnosis of chronic calculus cholecystitis and can be used at all level of health care center. All the cholecystectomy specimens operated for symptomatic gall stone diseases are must sent for histopathological examination to rule out incidental gall bladder carcinoma. J. Dhaka National Med. Coll. Hos. 2025; 31 (01): 08-13